Application of Lactobacillus paracasei LPC02 and lactulose as a potential symbiotic system in the manufacture of dry-fermented sausage. (March 2019) - Coelho, Samira Reis; Lima, Ítalo Abreu; Martins, Maurilio Lopes; Benevenuto Júnior, Augusto Aloísio; Torres Filho, Robledo de Almeida; Ramos, Alcinéia de Lemos Souza; Ramos, Eduardo Mendes
Abstract: The purpose of this study was to evaluate how the incorporation of the probiotic culture Lactobacillus paracasei and the prebiotic lactulose in dry-fermented sausage affects the technological, microbiological and sensorial characteristics of the products. Four formulations were analyzed: CONT (without prebiotic or probiotic); PREB (with 2% lactulose); PROB (with 10 8  CFU/g of L. paracasei ); and SYMB (with 2% lactulose and 10 8  CFU/g of L. paracasei ). The functional ingredients did not affect (P > 0.05) the water activity, pH, moisture, acidity and lactic acid bacteria counts during ripening process. Lower (P < 0.05) residual nitrite values were observed in sausages added with probiotic (7.20 ± 1.32 mg NO2 /kg) than in the other treatments (11.38 ± 3.21 mg NO2 /kg). The proximate composition and the sensorial attributes were not affected (P > 0.05) by the treatments. A mean concentration of 2.16 ± 0.39% of lactulose was observed in PREB and SYMB sausages and a count of 7.59 ± 0.37 log CFU/g of L. paracasei was observe in PROB and SYMB sausages. The incorporation of lactulose and L. paracasei into this traditional meat product resulted in a potential probiotic and symbiotic salami, adding additional nutritional benefits for the consumer. Highlights: Probiotic L paracasei and prebiotic lactulose in salami were evaluated. Functional ingredients did not change the characteristics of the salamis. Functional ingredients did not change the sensory acceptance of the salamis. Adding L paracasei and lactulose resulted in a potential symbiotic salami.